ID 364 – Repetitive transcranial magnetic stimulation (rTMS) in hypoxic brain injury due to acute carbon monoxide poisoning: Case report. Issue 3 (March 2016) - Marei, A.; Rashed, H.; Abdelnasser, A.
Abstract : Objectives: In the present case study, we studied the effect of repetitive transcranial magnetic stimulation (rTMS) combined with hyperbaric oxygen therapy (HBOT) in a case of hypoxic brain injury after acute CO poisoning. The main goal of the present study was to evaluate potential long-lasting outcomes of standard rTMS protocols in hypoxic brain insult. Case presentation: A 23 year old female patient has been diagnosed with acute CO poisoning, complicated by ataxia, aphasia and cognitive impairment. Patient received 18 sessions of HBOT, with no significant improvement. Her MRI brain revealed hyperintense signals involving bilateral frontal, parietal, temporal, occipital and cerebellar regions. Patient started to show improvement after receiving 4 sessions of rTMS, patient started to show improvement, regarding her aphasia and ataxia and her follow up MRI brain showed reduced hyperintensities mainly in cerebellar region, bilaterally. Discussion: TMS has been used recently as a tool for therapeutic neuromodulation, which restores the interhemispheric interactions following insult by inhibiting the healthy cortex with frequencies ⩽ 1Hz, or by exciting the lesioned cortex with frequencies between 3 and 50 Hz. Conclusion: TMS is a useful non-invasive neuromodulation promising tool to influence the post-lesional motor recovery especially if started within few days of the insult.